(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
On the basis of the data from the herbarium materials and literature sources and their own field of research species composition of flora of vascular plants of bogs of Middle Pridnistrov’ya is installed which has 128 species, belonging to 2 divisions, 3 classes, 34 families and 65 genera. In carrying out structural-and-comparative analysis some differences in comparison with the wetlands territories of the Western Podillya, Eastern Galicia and Forest-steppe zone as a whole were revealed. Taxonomic structure of the flora of the studied bogs is typical for floras of the Holarctic. The analysis of the geographic structure has shown that among the higher vascular plants are dominated by species of wider distribution, which are connected with the peculiarities of the relief of the area. Biomorphology and ecology analysis have proved the advantage of species which are typical for this type of environment.